2012
DOI: 10.1097/mnm.0b013e32834f9b14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic assessment of intracranial tuberculomas using 11C-methionine and 18F-FDG PET/CT

Abstract: This preliminary study suggests that in newly diagnosed, untreated intracranial tuberculomas, 11C-methionine, like 18F-FDG, may have limited specificity in distinguishing it from a neoplastic lesion. However, it may play an important role in assessing the response to antitubercular treatment. Further studies are warranted to explore the potential of 11C-methionine in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
8
2
Order By: Relevance
“…In this study 3, the standardized uptake value ratio (lesion to contralateral brain area) in both of these conditions was significantly lower (range: 0.3–0.7) than that noted in patients with lymphoma (range: 1.7–3.1) with virtually no overlap of the uptake values. Contrary to this 3, in a recently reported case series studying intracranial tuberculomas 4, a relatively high lesion-to-normal gray matter uptake ratio was observed on both 11 C-methionine (1.8±0.38) and 18 F-FDG scans (1.64±0.26) in all newly diagnosed cases. The investigators concluded that 11 C-methionine, similar to 18 F-FDG, has limited specificity in distinguishing tuberculoma from neoplastic lesions 4.…”
contrasting
confidence: 79%
See 1 more Smart Citation
“…In this study 3, the standardized uptake value ratio (lesion to contralateral brain area) in both of these conditions was significantly lower (range: 0.3–0.7) than that noted in patients with lymphoma (range: 1.7–3.1) with virtually no overlap of the uptake values. Contrary to this 3, in a recently reported case series studying intracranial tuberculomas 4, a relatively high lesion-to-normal gray matter uptake ratio was observed on both 11 C-methionine (1.8±0.38) and 18 F-FDG scans (1.64±0.26) in all newly diagnosed cases. The investigators concluded that 11 C-methionine, similar to 18 F-FDG, has limited specificity in distinguishing tuberculoma from neoplastic lesions 4.…”
contrasting
confidence: 79%
“…Contrary to this 3, in a recently reported case series studying intracranial tuberculomas 4, a relatively high lesion-to-normal gray matter uptake ratio was observed on both 11 C-methionine (1.8±0.38) and 18 F-FDG scans (1.64±0.26) in all newly diagnosed cases. The investigators concluded that 11 C-methionine, similar to 18 F-FDG, has limited specificity in distinguishing tuberculoma from neoplastic lesions 4.…”
contrasting
confidence: 79%
“…[21][22][23][24] Other PET Tracers Preliminary data suggest a role for monitoring for other PET tracer such as Ga68 citrate, F18 ethylcholine, and C11 methionine. [107][108][109] In preclinical studies, 68 Ga labeled with triacetylfusarinine C and ferrioxamine E and [ 64 Cu] DOTA labeled Aspergillus fumigatus-specific monoclonal antibody are Aspergillus-specific tracers that may have a role in monitoring infections. 110,111 In TB, a tracer trehalose, a non-mammalian disaccharide is at the very early stage of development and has shown promise in TB imaging.…”
Section: Fdg Monitoring In Other Conditionsmentioning
confidence: 99%
“…Given these results, MET PET appears to be superior to NH 3 PET and FDG PET for detection of tumor lesions. However, increased uptake of these amino acid tracers is not specific as it has been observed in many NNL, including intracranial hemorrhages, cerebral infarctions, multiple sclerosis and brain abscess [16, 2427]. In this study, MET PET revealed low specificity for brain tumors, as 10 of 23 NNL (6 patients with inflammatory and abscess lesions, 1 demyelination, 2 infarctions and 1 hemorrhage) showed MET uptake positive.…”
Section: Discussionmentioning
confidence: 49%